Hubungan antara Hardiness dengan Efikasi Diri Akademik Mahasiswa UKSW yang Mengikuti Organisasi Lembaga Kemahasiswaan - Valennia Ratu Puspaningtyas; Heru Astikasari Setya Murti (Jurnal Kajian dan Penelitian Umum, 2026)
Students who are actively involved in student organizations often face both academic and organizational demands simultaneously, which has the potential to cause stress. This condition requires students to possess hardiness characteristics and academic self-efficacy in order to adapt optimally to various pressures. This study aims to examine the relationship between hardiness and academic self-efficacy among students of Satya Wacana Christian University (UKSW) who participate in student organization institutions. This research uses a quantitative approach with a correlational design. The research subjects consisted of 119 students from a sample of 251 student organization functionaries in the 2026 period, selected using random sampling from a population of 892 students. Data were collected using the Academic Hardiness Scale and the General Self-Efficacy Scale (GSE). Data analysis was conducted using correlation testing. The results showed that there was a significant positive relationship between hardiness and academic self-efficacy among UKSW students involved in student organizations (r = 0.510; p = 0.000). These findings indicate that the higher the level of students’ hardiness, the higher their academic self-efficacy. Students with high hardiness tend to be more capable of managing pressure, maintaining motivation, and viewing academic and organizational challenges as opportunities for personal development.